2021
DOI: 10.1021/acs.chemmater.1c01972
|View full text |Cite
|
Sign up to set email alerts
|

Architecting Layered Crystalline Organic Semiconductors Based on Unsymmetric π-Extended Thienoacenes

Abstract: Herein, we demonstrate that engineered end-cap substitution for unsymmetric extended π-cores effectively achieves well-ordered two-dimensional (2D) molecular packing and thus realizes high-performance organic semiconductors (OSCs). We developed phenyl- and decyl-substituted benzothieno­[6,5-b]­benzothieno­[3,2-b]­thiophenes (BTBTTs) as solution-processable OSCs, providing layered single-crystalline thin-film transistors with a hole mobility of up to 12 cm2 V–1 s–1. The compound formed a bilayer-type layered he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…11) with a phenyl group and an alkyl group separately located at the end of both sides. 280 The drop-cast crystalline films of Ph-BTBTT-C10 can reach a high mobility of 12.8 cm 2 V À1 s À1 . 280 Aiming at understanding the role of anti-/syn-in the charge transport properties of organic semiconductors, we have also summarized one critical review recently.…”
Section: Five-ring-fused Molecules Based On Three Thiophene Rings And...mentioning
confidence: 99%
See 2 more Smart Citations
“…11) with a phenyl group and an alkyl group separately located at the end of both sides. 280 The drop-cast crystalline films of Ph-BTBTT-C10 can reach a high mobility of 12.8 cm 2 V À1 s À1 . 280 Aiming at understanding the role of anti-/syn-in the charge transport properties of organic semiconductors, we have also summarized one critical review recently.…”
Section: Five-ring-fused Molecules Based On Three Thiophene Rings And...mentioning
confidence: 99%
“…280 The drop-cast crystalline films of Ph-BTBTT-C10 can reach a high mobility of 12.8 cm 2 V À1 s À1 . 280 Aiming at understanding the role of anti-/syn-in the charge transport properties of organic semiconductors, we have also summarized one critical review recently. 286 The performance statistics of five-ring-fused organic semiconductors in Fig.…”
Section: Five-ring-fused Molecules Based On Three Thiophene Rings And...mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24] We previously prepared organic salts composed of disulfonic acid that contained anthracene as a functional moiety and several alkylamines as an arrangementcontrolling moiety. 25 We demonstrated that the π-stack structure of anthracene and the layered crystal structures formed by the disulfonic acid and alkylamine in the organic salts (layered crystallinity 26 ) were significantly altered depending on the type of alkylamine, without changing the structure of the functional moiety. However, to fully understand the relationship between the molecular arrangement and the functions of functional organic molecules, ideally, a method for systematically and precisely controlling their molecular arrangement without affecting the layered crystallinity is required.…”
Section: Introductionmentioning
confidence: 97%
“…[1]Benzothieno[3,2‐b][1]‐benzothiophene (BTBT) derivatives, as one of the most widely studied semiconductors in outstanding organic field‐effect transistors (OFETs), [ 34 , 35 , 36 , 37 , 38 ] are of great potential in solar‐blind photodetectors due to their wide band gaps ( E g ) and high mobility. Indeed, the star molecule C8‐BTBT was reported with high mobility and excellent solar‐blind photo response performance, and was expected to boom the organic solar‐blind photodetectors, [ 7 , 39 , 40 ] yet, the poor thermal stability of C8‐BTBT limits its in‐depth applications in photodetectors.…”
Section: Introductionmentioning
confidence: 99%